Analisis Editor Laman Web Dalam Pembangunan Aplikasi E-Dagang - Mohd. Nizam, Saad (2001)

(untitled)
Web Page Editors can be the complementary tools to simplify the design process of E-Commerce web pages. Creativity and willingness to explore all utilities from these tools is the gap that differentiates expert and novice. Research themes or questions concerning updated features of E-Commerce, the utilities of web page editor and assessment of the most demanding editor are outlined. Experts from MSC (Malaysian Super Corridor) status companies were selected as respondents. Generally, web page editors which support up-to-date web technology and easy to use interface are likely to become the first choice. Based on the analysis and result obtained from the study, some recommendations are presented to web developers who are interested in setting up E-Commerce web sites.